A comparative study of 'rhetorical criticism', ancient and modern - with special reference to the larger structure and function of the epistle of Jude - Wendland, E. R. (Neotestamentica, 1994)
Rhetoric, the so-called 'art and technique of persuasion', has been systematically studied with reference to oral and written literary discourse since Greek and Roman Classical times. In recent years the principles and techniques (CR) of the early rhetoricians have been the object of a revival of scholarly interest and have been utilised, in one form or another, as the basis for analysing the various writings of the Greek Testament, the epistles in particular. One such application provides a starting point for the present study, namely, Watson's (1988) analysis of 'invention, arrangement, and style' in the book of Jude. A summary of the results of Watson's classically oriented investigation is compared with a new examination of this letter according to the methodology of what has been termed 'rhetorical criticism' RC), an approach pioneered by James Muilenburg in the 1960s (eg 1969) and applied by his followers largely to Old Testament literature. The pros and cons of each analytical technique are discussed (with reference, also to such important studies as Bauckham 1983, Stowers 1986, and Neyrey(1993) and a mutually complementary, more macrotext-orientated procedure is then proposed. This essay concludes with a brief overview of its implications for the ongoing structural- stylistic and rhetorical-critical investigation of biblical literary works, Old Testament as well as New Testament, in their diverse socio-religious settings, both ancient and modern.